Pengaruh Keselamatan dan Kesehatan Kerja (K3) dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan Mie Gacoan Ratulangi - Prayogo, Muh Agung; Anwar; Dipoatmodjo, Tenri S.P.; Musa, Muhammad Ichwan; Rahman, Abdul (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
Occupational safety and health as well as work motivation are important factors in human resource management that can influence employee job satisfaction. A safe and healthy work environment, supported by good work motivation, will increase employee comfort and enthusiasm in carrying out their duties. This study aims to analyze the effect of Occupational Safety and Health (OSH) and work motivation on employee job satisfaction at Mie Gacoan Ratulangi, both partially and simultaneously. This study uses a quantitative approach with a survey method. The population in this study consisted of all employees of Mie Gacoan Ratulangi totaling 65 people. The sampling technique used was saturated sampling, so that all members of the population were used as research samples. Data were collected through the distribution of questionnaires using a five-point Likert scale and analyzed using multiple linear regression analysis with the help of IBM SPSS Statistics software. The results of the study indicate that (1) Occupational Safety and Health (OSH) has a positive and significant effect on employee job satisfaction, (2) work motivation has a positive and significant effect on employee job satisfaction, and (3) Occupational Safety and Health (OSH) and work motivation simultaneously have a positive and significant effect on employee job satisfaction at Mie Gacoan Ratulangi. The conclusion of this study shows that the implementation of a good occupational safety and health system and the provision of appropriate work motivation can improve employee job satisfaction. Therefore, companies need to continuously pay attention to the implementation of OSH and increase employee work motivation in order to create a safe, comfortable, and productive work environment.